2015
DOI: 10.1039/c5gc00286a
|View full text |Cite
|
Sign up to set email alerts
|

A straightforward metal-free synthesis of 2-substituted thiazolines in air

Abstract: A range of 2-substituted 4,5-dihydrothiazoles was easily synthesised from the reaction of nitriles with cysteamine in the presence of a catalytic amount of NaOH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Condensation of aminothiols with arylnitriles offers a convenient route for the synthesis of 2‐arylthiazolines. However, most of the transformations of nitriles and aminothiols into thiazolines involve the use of strong bases, or catalytic reagents such as cellulose sulfuric acid, phosphotungstic acid under microwave irradiation, Cu complexes, 1,3‐dibromo‐5,5‐dimethylhydantoin, or 1‐butyl‐3‐methylimidazolium tribromide . Even though these innovative synthetic strategies provide new routes for the synthesis of 2‐arylthiazolines, yet they usually suffer from a variety of drawbacks including harsh reaction conditions, use of strong bases, use of expensive and/or less abundant metal catalysts or reagents and limited substrate scope.…”
Section: Introductionmentioning
confidence: 99%
“…Condensation of aminothiols with arylnitriles offers a convenient route for the synthesis of 2‐arylthiazolines. However, most of the transformations of nitriles and aminothiols into thiazolines involve the use of strong bases, or catalytic reagents such as cellulose sulfuric acid, phosphotungstic acid under microwave irradiation, Cu complexes, 1,3‐dibromo‐5,5‐dimethylhydantoin, or 1‐butyl‐3‐methylimidazolium tribromide . Even though these innovative synthetic strategies provide new routes for the synthesis of 2‐arylthiazolines, yet they usually suffer from a variety of drawbacks including harsh reaction conditions, use of strong bases, use of expensive and/or less abundant metal catalysts or reagents and limited substrate scope.…”
Section: Introductionmentioning
confidence: 99%
“…Cazin conditions [ 32 ] provided a low yield for 25 ( Table 2 , experiment 1), observing an incomplete reaction. Lengthening the reaction time (experiment 2) did not improve the outcome, nor did a greater amount of base (experiment 3), which caused the yield to drop sharply due to the hydrolysis of benzonitrile to carboxylic acid.…”
Section: Resultsmentioning
confidence: 99%
“…20 While trying to expand this base-catalyzed protocol to the synthesis of 2-substituted oxazolines, using benzonitrile 1a and ethanolamine 2a as model substrates, we found that a catalytic amount of the base (10 mol%) was solely capable to promote this reaction (Table 1). Strong bases, such as alkali hydroxides (Table 1, entries 2 and 3) and tert-butoxides (Table 1, entry 4), gave only poor conversions, whereas slightly better results were obtained using weak bases, especially Na 2 CO 3 and NaOAc (Table 1, entries 6 and 9, respectively).…”
Section: Resultsmentioning
confidence: 99%